Bioactive Compounds from Marine Algae: Dual Benefits for Diabetes and Renal Health - Ch. Ramya, Ch. Ramya; Sowmya, Reena; Kumari, Anju; G. Mariappan, G. Mariappan; Pethe, Anil; Ingle, Rahul (Journal of Neonatal Surgery, 2025)
Bacterial cellulose (BC), a superior form of cellulose synthesized by various microbial genera, offers significant advantages over plant-derived cellulose due to its unique properties such as high crystallinity, excellent water-holding capacity, mechanical strength, and moderate biocompatibility. It is widely used in medical applications, such as wound dressings, tissue engineering and in dentistry, it is explored for guided tissue regeneration, dental implant coating, enhancing tissue integration and healing. Bacterial cellulose morphology is influenced by various factors including the microbial species, synthetic pathways, culture conditions and culture methods. Typically, it takes the form of a gelatinous membrane, while agitated or shaking culture methods yield fibrous networks. Bioreactor cultures offer controlled environment that enhance fiber length, diameter, alignment, and overall mechanical properties. The crystalline nanofiber network of BC directly influences its properties such as tensile strength, water retention, and elastic modulus. The choice of cultivation method and cultural conditions significantly impacts the morphology and properties of BC, enabling customization for specific needs and promoting its adoption in fields such as healthcare, biotechnology, and sustainable manufactur Marine algae, a varied and abundant group of aquatic organisms, have garnered attention for their rich content of bioactive components along with significant health advantages. Among these benefits, antidiabetic and nephroprotective properties of marine algae are particularly promising. Diabetes and chronic kidney disease (CKD) are prevalent global health issues. This review aims to comprehensively explore the bioactive compounds obtained from marine algae and their dual function in managing diabetes and promoting renal health. To comprehensively review the antidiabetic and nephroprotective potential of bioactive substances derived from marine algae, exploring their mechanisms of action and therapeutic prospects. A detailed literature review was conducted, focusing on the bioactive components from marine algae, including polysaccharides, polyphenols, peptides and their effects on diabetes and renal health. Mechanisms of action, key studies, and potential clinical applications were examined. Polysaccharides such as fucoidan, alginate, and laminarin improve glucose metabolism, enhance insulin sensitivity, and reduce postprandial glucose levels. Polyphenols like phlorotannins exhibit antioxidant properties, inhibit carbohydrate digestion enzymes, and protect pancreatic β-cells. Peptides from marine algae enhance insulin secretion and improve glucose uptake. In renal tissues, antioxidants like astaxanthin reduce inflammation and oxidative stress. Anti-inflammatory compounds, particularly fucoidan and polyphenols, mitigate renal inflammation and fibrosis. Marine algae are the prospective source of bioactive substances with dual antidiabetic and nephroprotective benefits. Future research should focus on clinical trials, improving bioavailability, and standardization of algal extracts to develop effective therapies.